Advances in biotechnological applications of waste cooking oil - Omojola Awogbemi (Elsevier, 2021)
Waste cooking oil (WCO) is generated when edible vegetable oil is used for frying food items. Inappropriate disposal of WCO exacerbates environmental pollution, block drains and contaminates terrestrial and aquatic habitats while its consumption deleteriously impacts human and animal health. In this review, the current efforts into the biotechnological conversion and applications of WCO as feedstock for biofuel, bisabolene, biolubricants, liquid detergents, dishwashing soap and aromatherapy candle, plasticizer, polyurethane foam, surfactants, asphalt rejuvenator are discussed. Aspects related to the global scenario of WCO generation, their physico-chemical properties and avenues of their utilization are also presented. These applications ensure appropriate utilization of WCO as valuable household commodities and industrial products. More investigations are needed for the deployment of WCO for the production of valuable products and to promote circular economy.